Research Mentorship for Medical Trainees Across the Continuum: A Faculty Toolkit - Cori Green; Su-Ting Li; Thanakorn Jirasevijinda; Susan Bostwick; Joy Howell; Erika Abramson (Association of American Medical Colleges, 2015)
Abstract Literature has shown that an effective research mentoring relationship not only influences personal and career development, but also increases productivity and success for both mentors and mentees. In academic medicine, faculty are often encouraged to mentor trainees in scholarly activity; however, faculty development and training in the area of research mentorship, is generally limited. It has become increasingly important, to both medical schools and residency/fellowship programs, to provide their trainees with meaningful scholarly training and activities. These tools can form the basis of a faculty development workshop or can be used independently by faculty engaged in mentoring trainees in a research project. The PowerPoint presentation and accompanying workshop materials are intended to be used in a 1-hour workshop delivered to faculty by program leadership, or a faculty member with expertise in this area. The intended audiences for this workshop and materials are physicians who mentor medical student, resident, or fellowship trainees in a scholarly activity project. The workshop can also be utilized by program leadership as a faculty development workshop to enhance their faculty's research skills and give them tools for the process of mentoring. These materials can also be integrated into current mentoring activities alone, without a faculty development workshop. We first piloted the cases and relationship building worksheets at an Academic Pediatric Association regional conference and then refined it at two national conferences. Based on the favorable reception and positive feedback generated by the workshops, the authors from Weill Cornell Medical Center were asked to develop and deliver a workshop to their local pediatric faculty on mentorship. This workshop was delivered during a regularly scheduled faculty meeting with the entire meeting dedicated to faculty development. Comments from workshop evaluations included "Great interactive workshop. Left with lots of practical tools." Another participant wrote "Very well presented in an order that made sense and with handouts and examples that accentuated the learning experience." A third person wrote "Mentoring ideas were excellent." Workshop participants recommended that the session be repeated the following year. These materials are also available to faculty and residents at each of our institutions and have been actively used by faculty and residents working on their required scholarly activity for over a year.